2011
DOI: 10.1111/j.1439-0272.2011.01220.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility suppression in male albino rats by administration of methanolic extract of Opuntia dillenii

Abstract: To control growing world population, there is a need for male contraceptive methods that are comparable to female contraceptives, but due to lack of knowledge or investigation, no sufficient safe and effective contraceptives were developed till now. In the present investigation, the effect of 100% methanol extract of Opuntia dillenii phylloclade on reproduction in male rats was studied. A first group (I) received vehicle alone to serve as control. The second group (II) was further divided into treated and reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…However, their studies did not show 100% efficacy of the extract on fertility suppression and reversibility. 23 However, in most of the studies, the effect of the plant extract on fertility was only partial and, In our study, treatment of the extract of O. elatior has shown marked decline in epididymal sperm count and motility in rats which was dose-dependent being 80% at the highest dose. The fertility of the treated male rats was suppressed in both dosage groups, being 100% at the high dose.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…However, their studies did not show 100% efficacy of the extract on fertility suppression and reversibility. 23 However, in most of the studies, the effect of the plant extract on fertility was only partial and, In our study, treatment of the extract of O. elatior has shown marked decline in epididymal sperm count and motility in rats which was dose-dependent being 80% at the highest dose. The fertility of the treated male rats was suppressed in both dosage groups, being 100% at the high dose.…”
Section: Discussionmentioning
confidence: 49%
“…[19][20][21] Extracts of the phylloclade of O. dillenii have been reported to show antispermatogenic effect and fertility suppression in the laboratory rat. 22,23 O. elatior is a common cactus in southern India and there is an unsubstantiated claim of its use in folk medicine for fertility control. 24 In view of the potential of Opuntia as a source of male antifertility agent, this study was undertaken to investigate the male antifertility activity of the fruit pulp of O. elatior with regard to sperm production, steroidogenesis, fertility and its reversibility.…”
Section: Introductionmentioning
confidence: 99%
“…Sertoli cells also constitute to the blood-testis barrier, thus damage to Sertoli cells may lead to impairment of male reproduction. Hence, the degeneration of seminiferous tubule and Sertoli cells supported the antispermatogenic effects of AP extracts on male rats (Bajaj & Gupta 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Reduction of testosterone level in the treated group might have effects on spermatogenesis, cellular structures and other male reproductive functions such as the inhibition of gonadotropin-releasing hormone, luteinizing hormone secretion, induction and maintenance of differentiation of male accessory reproductive organs and hence, reduction in sperm count (Bajaj & Gupta 2011;Shkukani et al 2007). Studies on other plant, for example Centella asiatica L. extract as male antispermatogenic and antifertility agents, demonstrated that the decrease in the level of serum testosterone resulting in the decrease of sperm quality (Yunianto et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The androgens play pivotal role of in spermatogenesis male fertility 111,112,113 . The testosterone main testicular androgen produced by Leydig cells under the influence of LH, LH secretion in turns regulated by hypothalamic GnRH.…”
Section: Discussionmentioning
confidence: 99%